Effects of the Polypropylene Oxide Number on the Surface Properties of a Type of Extended Surfactant. Issue 3 (14th April 2018) - Lv, Mengdie; Zhou, Yawen; Wang, Shan; Han, Fu; Xu, Baocai
Abstract: The surface properties of 5 extended surfactant C12–14 P m E2 S solutions in pure water and 0.1 M NaCl were investigated through surface tension and electrical conductivity measurements. The surface properties measured include the critical micelle concentration (CMC), critical surface tension ( γ cmc ), maximum surface excess concentration ( Γ max ), minimum area occupied per surfactant molecule ( A min ), and efficiency in surface tension reduction (pC20 ). The CMC values of the 5 surfactants decreased with increasing polypropylene oxide number (PON) and were higher than those obtained in 0.1 M NaCl. The Γ max values showed a downward trend whereas the A min values exhibited an upward trend with increasing PON without NaCl. The Γ max values were higher and the A min values were lower than those obtained without 0.1 M NaCl. The CMC values increased at elevated temperatures. The CMC values of C12–14 P3 E2 S, C12–14 P5 E2 S, and C12–14 P8 E2 S were similar but were markedly lower than those of C12–14 E2 S at different temperatures. When PON was less than 12, the log CMC value decreased linearly with increasing PON in the absence of salt, and the relationship between pC20 and PON was linear. But in the presence of 0.1 M NaCl, the log CMC value decreased exponentially with increasing PON.